Regulation of the Transferrin Receptor Recycling in Hepatitis C Virus-Replicating Cells - Haberger, Vanessa; Elgner, Fabian; Roos, Jessica; Bender, Daniela; Hildt, Eberhard (Frontiers in Cell and Developmental Biology, 2020)
After binding of its ligand transferrin, the transferrin receptor (TfR) is internalized via early endosomes. Ligand and receptor can be recycled. α-Taxilin was identified as an essential factor for TfR recycling. Apart from its role for iron uptake, TfR is a coreceptor for hepatitis C virus (HCV) infection. In HCV-replicating cells, the amount of a-taxilin is decreased. This study aims to investigate the effect of decreased α-taxilin levels in HCV-replicating cells on recycling of TfR, its amount on the cell surface, on iron uptake, and the impact of a disturbed TfR recycling on HCV superinfection exclusion. TfR amount and localization were determined by CLSM and surface biotinylation. α-taxilin expression was modulated by CRISPR-Cas9 knockout, siRNA, and stable or transient overexpression. For analysis of HCV superinfection fluorophor-tagged reporter viruses were used. The amount of α-taxilin is decreased in HCV-infected cells. In accordance to this, the protein amount of TfR is significant lower in HCV-positve cells as compared to the control, while TfR expression is not affected. Due to the impaired recycling, internalized TfR is degraded by the endosomal/lysosomal system. The significant lower number of TfR molecules on the cell surface is reflected by reduced transferrin binding/internalization and strong reduction of intracellular iron level. Overexpression of α-taxilin in HCV-replicating cells rescues TfR recycling, augments TfR on the cell surface, and restores transferrin binding. The block of superinfection in HCV-replicating cells could be overcome by overexpression of α-taxilin. Taken together, the diminished level of α-taxilin in HCV-replicating cells prevents recycling of TfR leading to decreased transferrin binding and iron uptake. Disappearance of TfR from the cell surface could be a factor contributing to the exclusion of superinfection by HCV.